Novelty technique in bleaching of 100% cotton ring-spun yarns and knitted fabrics - (:unkn) unknown (TEXTILE INST, 2004)
Bleaching is an important and specific step of textile-wet processes, which improves the absorbance capabilities of textile materials. Using ultrasonic energy in textile properties especially in bleaching is an alternative method for conventional applications. This study is about the hydrogen peroxide bleaching of 100% cotton Spun yarns and knitted fabrics produced from the same yarns. In this work first, cotton spun yarns were treated with H2O2 at different temperatures and times, later knitted fabrics produced from these yarns were bleached with H2O2 at the same conditions of both in ultrasonic energy bath and conventional methods and their whiteness index were measured spectrophotometrically. The overall results of the ring-spun yarns were also statistically analysed.